Alkaloid-rich fraction from Luffa cylindrica Linn fruit enhances memory and mitigates oxidative stress in hippocampus of ozone-exposed sprague Dawley rat via LCMS and network pharmacology approach - Ankul Singh S; Chitra Vellapandian (Ecotoxicology and Environmental Safety)
Luffa cylindrica (L.), is a medicinal plant aimed to investigate the efficacy of the alkaloid-rich fraction (ARF) extracted from L. cylindrica. The study employed behavioural analysis of rat using Morris water maze (MWM), biochemical analysis of apoptotic proteins, Immunohistochemistry of caspase 3 protein and network pharmacology approach. The ozone-induced group exhibited complex behavioral changes. Western blot analysis revealed altered expression of SOD2, Caspase 3, and Cytochrome C which play integral roles in oxidative stress, apoptosis, and mitochondrial function. Histopathological analysis of the hippocampus further supported the neuroprotective potential of L. cylindrica, demonstrating a reduction in neuropathological lesions and improved memory processes. Network Pharmacology showed the implication of GSK3β in neuronal damage. ARF showed promise in preventing further neuronal damage. In summary, this comprehensive study sheds light on its potential in neuroprotective applications by in vivo behavioral and molecular analyses. It provides a holistic understanding of the medicinal properties of ARF, encouraging further exploration for potential therapeutic interventions in neurological diseases.